Comparison study of procedures for aspiration of biopsy samples - Mendonça, Paula (2016)
Introduction: The samples obtained from fine needle aspiration in liquid base cytology (FNAC) are often limited by scarce cellularity compared to the amount of colloid and presence of blood. Accordingly, it was important to test alternative technical procedures so as to maximize the cellularity of each sample. Objective: To compare the morphological features and cellularity of the three procedures in the FNAC cytodiagnosis of the thyroid. Methods: A total of 31 cases were each subjected to a cell block and ThinPrep preparation as well as a routine smear. The observation and analysis was performed using an optical microscope. Cytological diagnosis of each cell block case was objectively analysed for cellularity, presence of background and cellular preservation. Each smear and ThinPrep case was analysed for the presence or absence of cells. The data was analysed with Microsoft Excel (Office 2010) and SPSS (Statistical Package of Social Science) version 15.0 for Windows. Results: Of 31 cases, only 20 had thyroid cells in the cell block and ThinPrep preparations, however, all smear cases contained thyroid cells. Some background was found in 30 Cell block cases with only 5 of these containing well preserved cells for cytodiagnosis. Conclusions: As indicated by the results, smear is the most appropriate procedure for FNAC of the thyroid.